Global health risks mortality and burden of disease attributable to selected major risks (World Health Organization, 2009)
This publication is a comprehensive assessment of leading risks to global health. It provides detailed global and regional estimates of premature mortality, disability and loss of health attributable to 24 global risk factors.--Publisher's description.